Relation of birth weight and childhood respiratory infection to adult lung function and death from chronic obstructive airways disease. Issue 6804 (21st September 1991) - Barker, D J; Godfrey, K M; Fall, C; Osmond, C; Winter, P D; Shaheen, S O
Abstract : OBJECTIVE–To examine whether birth weight, infant weight, and childhood respiratory infection are associated with adult lung function and death from chronic obstructive airways disease. DESIGN–Follow up study of men born during 1911-30 whose birth weights, weights at 1 year, and childhood illnesses were recorded at the time by health visitors. SETTING–Hertfordshire, England. SUBJECTS–5718 men born in the county during 1911-30 and a subgroup of 825 men born in the county during 1920-30 and still living there. MAIN OUTCOME MEASURES–Death from chronic obstructive airways disease, mean forced expiratory volume in one second (FEV1) and forced vital capacity (FVC), and respiratory symptoms. RESULTS–55 men died of chronic obstructive airways disease. Death rates fell with increasing birth weight and weight at 1 year. Mean FEV1 at age 59 to 70 years, adjusted for height and age, rose by 0.06 litre (95% confidence interval 0.02 to 0.09) with each pound (450 g) increase in birth weight, independently of smoking habit and social class. Bronchitis or pneumonia in infancy was associated with a 0.17 litre (0.02 to 0.32) reduction in adult FEV1 and with an increased odds ratio of wheezing and persistent sputum production in adult life independently of birth weight, smoking habit, and social class. Whooping cough in infancy was associated with a 0.22 litre (0.02 to 0.42) reduction in adult FEV1. CONCLUSIONS–Lower birth weight was associated with worse adult lung function. Intrauterine influences which retard fetal weight gain may irrecoverably constrain the growth of the airways. Bronchitis, pneumonia, or whooping cough in infancy further reduced adult lung function. They also retarded infant weight gain. Consistent with this, death from chronic obstructive airways disease in adult life was associated with lower birth weight and weight at 1 year. Promoting lung growth in fetuses and infants and reducing the incidence of lower respiratory tract infection in infancy may reduce the incidence of chronic obstructive airways disease in the next generation.